Optimization of TiC Content during Fabrication and Mechanical Properties of Ni-Ti-Al/TiC Composites Using Mixture Designs - Lee, Dong-Jin (Materials (Basel), 2018)
Ni-Ti-Al alloys are highly promising materials for use in high-temperature structural materials. However, minimal research has been conducted to improve the associated mechanical properties through secondary phase addition. In this study, Ni-Ti-Al/TiC composites were fabricated at a pressure of 40 MPa and a sintering temperature of 1050 °C using spark plasma sintering. The microstructure and interfacial structure were analyzed by scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray diffraction analysis. Microscopic analysis revealed that TiC particles interacted with Ti and Al, resulting in the formation of Ti(2)AlC, which promoted chemical metallurgical bonding between the Ni–Ti–Al alloy and TiC. Wear characteristics were measured using the wear test with a ball on disk. It was confirmed that the 40 wt % specimen had the highest hardness due to pores generated inside, but the wear amount was relatively high. The mixture design of a minitap was proceeded using hardness, bending strength, and wear loss. An optimum composition ratio of 32.16 wt % was determined using the composite desirability of the three properties.